1989
DOI: 10.1002/ijc.2910440509
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of c‐myc and c‐erbB‐2 proto‐oncogenes in human solid tumors: Frequency and clinical significance

Abstract: Molecular probes for cellular proto-oncogenes have recently been extensively used in order to search for functional and structural alterations in tumor tissues. Variable, and sometimes contradictory, results have been obtained regarding the frequency and clinical significance of amplification of the c-myc and c-erbB-2 proto-oncogenes in different series of human solid tumors. We addressed this question by performing Southern blotting analysis on 131 primary adult solid tumors of various tissues and 5 metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…All of these factors are considered to be bad prognostic indicators. According to other authors there was no correlation with tumour size (Gutman et al, 1989;Seshadri et al, 1989) and age at diagnosis (Zhou et al, 1987;Seshadri et al, 1989).…”
mentioning
confidence: 89%
“…All of these factors are considered to be bad prognostic indicators. According to other authors there was no correlation with tumour size (Gutman et al, 1989;Seshadri et al, 1989) and age at diagnosis (Zhou et al, 1987;Seshadri et al, 1989).…”
mentioning
confidence: 89%
“…A characteristic example is the alleged association between Myc amplification and poor prognosis, which is suggested by some studies, [39][40][41][42][43] but refuted by others. [44][45][46][47] Nevertheless, some expression profiling analyses 48 support a correlation between Myc levels and poor breast cancer outcome. In addition, an analytical approach integrating expression and copy number profiles 49,50 has indicated that the so-called "wound response" expression signature previously associated with poor overall survival and increased risk of metastasis in breast cancer 51 can be correlated with a coordi- nate amplification of Myc and Cops5 (a gene encoding one of the subunits of the Cop9 signalosome).…”
Section: Myc In Normal Human Breast and Breast Cancermentioning
confidence: 99%
“…c-erbB-2 amplification and overexpression have been observed in several human tumors (18,19). In head and neck carcinomas, the frequencies of erbB-2 amplification and overexpression range from 0 to 41% (20)(21)(22).…”
Section: Genetic Alterations Oncogene Activationmentioning
confidence: 99%